The Moral Universe: A Survey of Undergraduate Student Attitudes towards Plagiarism - Kaler, Michael; Richter, Christoph; Scoville, Chester; Szigeti, Steve (Canadian Perspectives on Academic Integrity, 2023)
In this article, we present early results of surveys conducted at the University of Toronto, Mississauga campus, across four terms (January 2020 to December 2021) of early-year undergraduate students to determine their understanding and views of plagiarism. Our survey instrument gathered basic demographic information as well as asked participants to respond to 24 statements using a 5-point Likert scale. We share our analysis of responses to 15 statements in the survey which were intended to provide an understanding of the “moral universe” of students—that is, the way that they contextualize plagiarism in terms of their moral standards. Our major finding is that although students across three disciplines (Humanities, Social Science, and Science) recognized the potential harm of plagiarism to the value of their degrees, they also believed self-plagiarism to be less serious than other forms of academic integrity offences. We consider how the moral universe of students differs from the moral universe implied in the University’s codes and argue that the messaging used by academic institutions should convey the reasons for taking plagiarism seriously. We argue that presenting plagiarism as similar to theft of property rather than an issue of pedagogy might inadvertently encourage students to consider self-plagiarism to be more acceptable than other forms of plagiarism.